TREATMENT OF INTRA-ARTICULAR FRACTURES OF THE DISTAL HUMERUS - Ashirov M.U; Turdiyev S.B; Poyanov Mirkomil Shavkat o'g'li; Daminov Shohruh Isomidin o'g'li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Treatment of intraarticular fractures of the distal end of humerus. Radiographs of 27 patients with intraarticular humerus fractures aged 21 to 60 years (median - 37 years old) were analyzed, 17 of them were men and 10 women: they had remoteness of the fracture zone from the proximal metaphysis of the humerus, the length of the fracture zone and size displacements of fragments. In the statistical analysis of the actual data the mean, standard deviation was calculated. An analysis of the sample, including comminuted intraarticular fractures of the humerus, showed that the fracture level was in the range of 40.9±19.9%, ranging from 11.6% to 72.4% in length. Between the  length  of  the  fracture  and  the  period  of  consolidation,  there  was  a  statistically significant positive moderate link. The term of fusion of the fracture of the distal end of  the  humerus  correlates  with  the  following  characteristics:  1)  the  location  of  the fracture: the closer location of the fracture to the distal end of the humerus, the shorter fusion period; 2) the length of the fracture zone: the greater length of the fracture zone, the longer the fusion period; 3) the post-repositional value of the displacement of the fragments: the larger value of the post-repositional displacement of the fragments, the longer term of fusion. The revealed dependences are valid for fractures of the humerus in the range from 11 to 72% of the distance of the fracture from the proximal end of the humerus.